Biochemical and Functional Characterization of Glycoside Hydrolase Family 16 Genes in Aedes aegypti Larvae: Identification of the Major Digestive β-1,3-Glucanase - Souza, Raquel Santos; Gama, Maiara do Valle Faria; Schama, Renata; Lima, José Bento Pereira; Diaz-Albiter, Hector Manuel; Genta, Fernando Ariel (Frontiers in Physiology, 2019)
Insect β-1,3-glucanases belong to Glycoside Hydrolase Family 16 (GHF16) and are involved in digestion of detritus and plant hemicellulose. In this work, we investigated the role of GHF16 genes in Aedes aegypti larvae, due to their detritivore diet. The genome of Ae. aegypti contains six genes coding for GHF16 proteins (Aae GH16.1 - Aae GH16.6), containing 2-6 exons. Phylogenetic analysis suggests that Aae GH16.1, 2, 3, 5 and 6, which contain the GHF16 conserved catalytic residues, are related to other insect glucanases. These genes suffered duplications in the genomes of Nematocera. Aae GH16.4 is related to β-1,3-glucan binding proteins, which have no catalytic activity and are involved in the activation of innate immune responses. Additionally, Ae. aegypti larvae contain significant β-1,3-glucanase activities in the head, gut and rest of body. These activities have optimum pH about 5-6 and molecular masses between 41 and 150 kDa. All GHF16 genes above showed different levels of expression in the larval head, gut or rest of the body. Knock-down of AeGH16.5 resulted in survival and pupation rates lower than controls (dsGFP and water treated). However, under stress conditions, severe mortalities were observed in AeGH16.1 and AeGH16.6 knocked-down larvae. Enzymatic assays of β-1,3-glucanase in AeGH16.5 silenced larvae exhibited lower activity in the gut and no change in the rest of the body. Chromatographic activity profiles from gut samples after GH16.5 silencing showed suppression of enzymatic activity, suggesting that this gene codes for the digestive larval β-1,3-glucanase of Ae. aegypti. This gene and enzyme are attractive targets for new control strategies, based on the impairment of normal gut physiology.